Dull life, you don't have to be that way-- : an essay submitted in partial fulfillment of the requirements for the degree of Master of Design, Massey University, Wellington, New Zealand, 2011 - Bartels, Kate (Massey University, 2011)
Dull life, you don’t have to be that way is an exploration of the global phenomenon the Online Fashion Realm has recently become, and of the way in which geographic fashion ‘outsiders’ can inhabit this domain, whilst being removed from the physical epicenters of fashion. The Fashion Blogosphere, as a now integral part of this Online Fashion Realm, has enabled a seemingly global democratization of the fashion system that previously existed as a realm of controlled access. This blogosphere has granted ‘access’ to fundamentally change the tradition-etched fashion system from a monologue to a ‘conversation’ - a conversation in which everyone has a supposed equal opportunity to participate (Scherpe, 2010). This project is a journey of gathering and gleaning within the virtual online world, and within the ‘real’ offline world, as an ‘outsider’ fashion designer situated in New Zealand. I am a muser exploring the potential ways that I can infiltrate this new digital space with my own designed and made garments and images, to form my designer identity by what I disseminate, but equally by how. I am testing how much of this fashion conversation I can become a part of by the inception of my own blog www.dulllifeyoudonthavetobethisway.tumblr.com and by the dissemination of my finished works on its successor, an independent website www.dulllifeyoudonthavetobethatway.com. I’ve preceded to build a ‘genuine-façade’, and an ‘elusive reveal’ of my ‘brand’. I’ve constructed a visual presence through the realisation of mood within designed garments and images to exist online and thus attempt to generate a multimedia conversation. This writing is a ‘ficto-critical’ reflection of my processes as a continuation of my design practice. The entirety of this project functions as a test for myself to see if I think I have what it takes to remain optimistic as an unknown fashion designer striving to have my designs embraced, initially only as images. This project is a reconnaissance mission, in which I have gathered and gleaned possibilities, and certified the criteria for, and essense of my ‘brand’, and it is still to be seen, what this may grow and flourish into.
Keywords: Fashion online; Fashion blogosphere; Design practice; Fashion design